ANALISIS PUTUSAN HAKIM PENGADILAN AGAMA PALEMBANG TENTANG PEMBATALAN PERKAWINAN MENURUT HUKUM ISLAM - Erik Rahman Gumiri (Usroh: Jurnal Hukum Keluarga Islam, 2021)
The issue of abolition of wedding is one of issue in family. For islamic the cancellation of wedding mentioned as fasakh. Fasakh is the abolition of the agreement of marriage because of the abolition occurs when the terms and pillars of marriage uncomplete in a marriage. The effect of the abolition in a marrige made the bond between spouse is disengaged from the court of judgement. The object study of this research is number of decision from: 0457/Pdt.G/2011/PA.Plg). This research desire to explain what about to be the primary consideration from judge in the court of religious in Palembang to decide and grant suit into number of decision from: 0457.Pdt.G/2011/PA.Plg and how perspective of islamic law towards primary decision of the judge into number of decision from: 0457/Pdt.G/2011/PA.Plg. The research discover that the primary of judge’s decision to decide and grant suit of abolition of marriage from number of decision from: 0457.Pdt.G/2011/PA.Plg is due to the wedding between petitioner and defendant to be held by illegitimate guardian, which is in this issue that to be wedding guardian is the assistant of note-taker of marriage (P3N) who claim as guardian judge whereas P3N is not guardian judge. As for the perspective of islamic law towards primary of judge’s consideration to decide case of the abolition of wedding is based on Syafi’i sect, the guardian of wedding as the valid requirement, if wedding without the guardian, or wedding without the guardian’s permit or any guardian but have no right to be guardian wedding, therefore a wedding have to be abolished. Key Words: Religious Court Decision, Cancellation of Marriage, Fasakh, Islamic Law.